Pengaruh Alat Pembayaran Menggunakan Kartu dan Uang Elektronik Terhadap Jumlah Uang Beredar M1 di Indonesia - Aurelia Savina; M Ridwansyah; Erni Achmad (PT. Hasba Edukasi Mandiri, 2026)
The development of digital technology has driven significant changes in the amount of money in circulation, especially in the last decade. One of the prominent phenomena of this change is the increase in non-cash transactions during transactions. This study aims to determine the development and analyze the influence of credit card transaction values, ATM/Debit card transaction values, and Electronic Money transaction values on the amount of money in circulation (M1) in Indonesia for the period 2010-2024. The data used in this study are secondary data sourced from Bank Indonesia (BI) and the Central Statistics Agency (CSA). This study uses a descriptive quantitative approach with a multiple linear regression method using Eviews12 software. The results of the study show that (1) The average development in the value of credit card transactions during the period 2010-2014 was 8 percent, the value of ATM/Debit card transactions was 10 percent, the value of electronic money transactions was 95 percent, and the amount of money in circulation M1 was 12 percent; and (2) The results of the multiple linear analysis show that the variables of credit cards, ATM/Debit and electronic money partially and simultaneously have a significant effect on the amount of money in circulation M1 in Indonesia.